Parenting Relationships With Stunting Incidence In Toddlers Aged 12-59 Months In Pasirhaur Village In 2022 - Irma Puspita Handayani; Mariyani Mariyani (Lembaga Pengembangan Kinerja Dosen, 2023)
The World Health Organization (WHO) estimates that the prevalence of parenting and stunting worldwide is 22 percent or as many as 149.2 million in 2020. Stunting is caused by multi-dimensional factors and not only caused by malnutrition experienced by pregnant women and children under five, another cause is poor parenting practices, including the lack of knowledge of mothers about health and nutrition before and during pregnancy, as well as after mothers give birth. Purpose of Writing : To determine the relationship between parenting style and the incidence of stunting in toddlers aged 12-59 months in Pasirhaur village in 2022. Research Methods : Case control research with a quantitative approach. A sample of 82 mothers with toddlers in November 2022. The sampling technique used is non-probability sampling with purposive sampling method. Results of the study : Poor parenting styles were more common in cases of stunting, with 31 people (75.6%) than good parenting styles for stunted toddlers, with 10 people (24.4%). In the chy-square test, the results of parenting variables for mothers' knowledge were lacking P value 0.008 <0.05, Not exclusive breastfeeding P value 0.03 <0.05, not MP-ASI P value 0.055 <0.05 , and care for sick children who lack P value 0.012 <0.05, so the analysis is that there is a relationship between parenting parents and stunting in toddlers aged 12-59 months in Pasirhaur Village in 2022. Conclusion : Good parenting can reduce the risk of stunting in toddlers and it is hoped that health workers, especially midwives